Mosques in Scandinavia: The Role of Language in Territorialisation Processes - Rosendal, Tove; Nielsen, Helle Lykke; Löfdahl, Maria (University of Gothenburg, 2026)
The data contains photos of architecture and visible inscriptions and texts both on the exterior of- and inside mosques, as well as photos documenting language choices by mosques online - on websites and in social media. The photos are taken in Copenhagen, Oslo and Stockholm in 2022.

Datamaterialet innehåller foton av arkitektur och synliga inskriptioner och texter både på utsidan av och inuti moskéer, samt bilder som dokumenterar moskéernas språkval på nätet – på webbplatser och i sociala medier. Bilderna är tagna i Köpenhamn, Oslo och Stockholm under 2022.
Moskéer i Skandinavien: Språkets roll i territorialiseringsprocesser
Keywords: online visibility; synlighet på internet; place names; ortnamn; religious buildings; religiösa byggnader; names; namn; texts; texter; choice of languages; språkval; architecture; arkitektur; visual design; visuell planering; buildings; byggnader; mosques; moskéer; bynames; binamn; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Interdisciplinary Studies in Humanities and Arts; Tvärdisciplinära studier i humaniora och konst; Geospatial; Geospatiala data; Buildings; Byggnader